Efficacy of Selected Plant Materials for the Control of Callosobruchus maculatus (F.) (Coleoptera: Bruchidae) on Stored Cowpea Seeds: A Review - Kashere M. A. (Current Research Progress in Agricultural Sciences Vol. 5, 2024)
Effect of Coffee senna (Cassia occidentalis), Shea butter (Vittallaria paradoxa), Neem (Azadirachta indica), Cashew (Anacardium occidentale (L)), Pipper guineense Schum, compared with Actellic dust (Pirimiphos methyl) on the control of cowpea bruchid, Callosobruchus maculatus (Fab.) under prevailing laboratory conditions were reviewed. The review showed that, at three days post-treatment, A. indica, and P. guineense caused 93.3% and 90%; adult mortality of C. maculatus at a rate of 0.8 g /20 g of cowpea seeds which was comparable with pirimiphos methyl that recorded 100% adult mortality at the same exposure period. However, at seven days post application, A. indica, P. guineense and pirimiphos methyl powders caused 100% mortality of adult bruchid at all tested concentrations. Similarly, the mixture of C. Occidentalis and V. paradoxa leaf powders in the ratios of 50%:50% applied at the rate of 2.5.5.0, 7.5 and 10.0w/w into 20g of cowpea seeds caused bruchid mortality at different time intervals with the highest mortality (100%) observed on the treated seed with the leaf powders combination applied at 7.5 and 10.0%w/w concentrations 24hours after treatment and was similar to what was recorded on seed treated with Pirimiphos methyl. Cashew kernel oil extract completely prevented infestation and damage of cowpea seeds for a period of three months with the steam distillate being the most toxic of all the extracts tested. The review clearly revealed the potentials of A. indica and P. guineense seeds powders and the mixed powders of leaves of C. occidentalis and V. paradoxa and cashew kernel oil as plant-derived grain protectants against C. maculatus and could serve as an alternative to synthetic insecticides for the protection of stored cowpeas against the bruchid.